Perempuan Melayu dalam Pemenuhan Ekonomi Rumah Tangga: Studi Kasus di Desa Senaning Kabupaten Batanghari - Fahmi Sy (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
This writing is aimed at discussing the role of Malay-Urban women in term of household economic effort. By employing anthropological approach, it is highlighted that women have important positions in economic life. It’s found that the Urban-Malay women play dominant role in sustaining economic needs both when they serve as wives and leader of thhe house. The engoing negative stereotype and prejudice developed recently toward them are now questioned, deniable with the proofs of their innovative roles they play in sustaining their economic life